Zachowania zdrowotne kobiet w okresie menopauzalnym = The health behavior of women during menopausal period - Weber-Rajek, Magdalena; Lubomska, Marta; Radzimińska, Agnieszka; Lulińska–Kuklik, Ewelina; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Weber-Rajek Magdalena, Lubomska Marta, Radzimińska Agnieszka, Lulińska–Kuklik Ewelina, Goch Aleksander, Zukow Walery. Zachowania zdrowotne kobiet w okresie menopauzalnym = The health behavior of women during menopausal period. Journal of Education, Health and Sport. 2016;6(2):151-162. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46353 http://ojs.ukw.edu.pl/index.php/johs/article/view/3395 https://pbn.nauka.gov.pl/works/715551 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. Zachowania zdrowotne kobiet w okresie menopauzalnym The health behavior of women during menopausal period Magdalena Weber-Rajek1, Marta Lubomska2, Agnieszka Radzimińska1, Ewelina Lulińska–Kuklik2, Aleksander Goch1, Walery Zukow3 1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy Katedra Fizjoterapii, Bydgoszcz, Polska / Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Physiotherapy, Bydgoszcz, Poland 2. Bydgoska Szkoła Wyższa, Bydgoszcz, Polska / University of Bydgoszcz, Bydgoszcz, Poland 3. Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska / Kazimierz Wielki University, Bydgoszcz, Poland Streszczenie Wstęp Menopauza to naturalny etap życia każdej kobiety. Zmiany hormonalne zachodzące w organizmie w tym okresie powodują często wiele dolegliwości. Jedną z metod łagodzenia objawów menopauzy jest stosowanie hormonalnej terapii zastępczej, jak również przestrzeganie zachowań sprzyjających zdrowiu. Hormonalna terapia zastępcza łagodzi objawy menopauzy, ale także niesie za sobą pewne zagrożenia, które można minimalizować poprzez zachowania prozdrowotne. Cel badań Celem badań była ocena zachowań zdrowotnych kobiet w okresie około menopauzalnym. Materiał i Metody W niniejszej pracy przebadano 50 kobiet w przedziale wiekowym 45-63 lata (średnia wieku 52,8 lat), które podzielono na 3 grupy w zależności od występowania objawów menopauzalnych i stosowania hormonalnej terapii zastępczej. Wyniki W badanej grupie kobiet w okresie menopauzalnym wykazano przeciętny poziom zachowań zdrowotnych. W całej badanej grupie najwyższe wyniki uzyskano w kategorii „zachowania profilaktyczne”, najniższe w kategoriach „prawidłowe nawyki żywieniowe” i „praktyki zdrowotne”. Porównując wyniki między grupami nie wykazano różnic istotnych statystycznie. Summary Introduction Menopause is a natural stage of life of every woman. The hormonal changes that occur the body often cause a lot of discomfort. One method of alleviating the symptoms of menopause is hormone replacement therapy, as well as the observance of behavior conducive to health. Hormone replacement therapy eases the symptoms of menopause, but also entails certain risks, which can be minimized by health behaviors. The aim of the study The aim of this reaserch was to present health behaviours of women in perimenopausal age. Material and Methods In this reaserch, 50 women in the age range 45-63 years old (average age 52,8) were examined and divided into 3 groups according to their menopausal symptoms and the use of hormonal replacement therapy. Results In the group of postmenopausal women showed an average level of health behavior. In the whole group achieved the highest scores in the category " prophylaxis behavior ", the lowest in terms of " proper nutrition habits " and "health practices". Comparing the results between the two groups showed no statistically significant differences. Słowa kluczowe: zachowania zdrowotne, kobieta. Keywords: health behaviors, female.